Assessment of SnO2 nanoparticles' impact on the growth of Picochlorum maculatum algae. Issue 12 (21st November 2022) - Bounnit, Touria; Ayesh, Ahmad I.; Saadaoui, Imen; Mohideen, Rihab S.; Sayadi, Sami
Abstract : Picochlorum maculatum – isolated from a Qatar marine environment, algal growth media are amended with different SnO2 nanoparticle concentrations (1, 5, 25, 50, and 100 mg L −1 ) and the culture was observed for 72 h. Abstract : To determine the effect of SnO2 nanoparticles on Picochlorum maculatum – isolated from a Qatar marine environment, algal growth media are amended with different nanoparticle concentrations (1, 5, 25, 50, and 100 mg L −1 ) and the culture was observed for 72 h. Algal growth, morphology, photosynthetic pigments and the potential for producing highly valuable biocompounds (including pigments, lipids, carbohydrates, etc. ) are investigated. The data obtained show that the SnO2 nanoparticles have a toxicity effect on the algae growth, with lower doses presenting more negative impacts than higher doses. The results of SEM observations highlight that the slow growth observed at 1–5 mg L −1 is triggered by the attachment of SnO2 nanoparticles to algal cells which caused dramatic damage to the cell morphology, cell shape, and size. However, at high concentrations of SnO2 (50–100 mg L −1 ), agglomeration of nanoparticles around the cells leads to a reduced effect on cell morphology and appearance. These data are supported by the energy dispersive X-ray spectroscopy (EDX) analysis of the cells after exposure to SnO2 . Moreover, the effects of nanoparticles on algae composition are dose specific. Lipids and carbohydrates are stimulated by the decrease in nanoparticle concentrations, while an inhibition in protein production is observed. Besides, the presence of SnO2 at low concentrations stimulates the synthesis of protective molecules such as carotenoids. Hence, exposure to SnO2 nanoparticles can be one of the methods to induce the synthesis of highly valuable products in the local microalgae, which can be used for many applications in different industries.